The effect of thermal ageing on the microstructure and fatigue strength of alloy 800HT. (18th December 2008) - Khan, Z.; Al-Habib, F.; Merah, N.; Allam, I.
This study explores the effect of ageing on the fatigue strength of alloy 800HT. In-service ageing-induced microstructural changes are simulated by pre-ageing the alloy specimens prior to fatigue testing. Ageing treatments at 650°C, 760°C and 870°C were carried out for periods of 24 h, 100 h, 500 h and 1000 h. An examination of aged specimens by optical and scanning electron microscopy reveals that intergranular and intragranular M23C6 type precipitates form during the ageing treatment. These precipitates produce a significant reduction in the fatigue strength of the alloy. The detrimental effect of pre-ageing is more pronounced at higher ageing temperatures and longer ageing times. These precipitate particles reduce the alloy fatigue strength via extensive secondary cracking due to the brittling effect of the precipitate particles.